Changes in Methylation Patterns of Tumor Suppressor Genes during Extended Human Embryonic Stem Cell Cultures - Kyung Min Kang; Jeoung Eun Lee; Ji Eun Park; Hyunjin Kim; Hee Yeon Jang; Minyeon Go; Dong Ryul Lee; Sung Han Shim (Hindawi Limited, 2021)
While studies on embryonic stem cells have been actively conducted, little is known about the epigenetic mechanisms in human embryonic stem cells (hESCs) in extended culture systems. Here, we investigated whether CpG island (CGI) methylation patterns of 24 tumor suppressor genes could be maintained during extended hESC cultures. In total, 10 hESC lines were analyzed. For each cell line, genomic DNA was extracted from early and late passages of cell cultures. CGI methylation levels of 24 tumor suppressor genes were analyzed using methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA), pyrosequencing, and real-time polymerase chain reaction (PCR). Different CGI methylation patterns of CASP8, FHIT, and CHFR genes were identified in between early and late passages in some hESC lines. CGI methylation levels of CASP8 significantly increased at late passage in CHA-36, CHA-40, and CHA-42 cell lines compared to those at early passage. The CGI methylation of the FHIT gene was higher at late passage than at early passage in CHA-15, CHA-31, CHA-32, and iPS (FS)-1 cell lines but decreased at the late passage in CHA-20 and H1 cell lines. Different CGI methylation patterns were detected for the CHFR gene only in iPS (FS)-1, and the level significantly increased at late passage. Thus, our findings show that CGI methylation patterns could be altered during prolonged ESC cultures and examining these epigenetic changes is important to assess the maintenance, differentiation, and clinical usage of stem cells.